Beyond the Warburg Effect: N-Myc Contributes to Metabolic Reprogramming in Cancer Cells - Yoshida, Go J. (Frontiers in Oncology, 2020)
Cancer cells generate large amounts of lactate derived from glucose regardless of the available oxygen level. Cancer cells finely control ATP synthesis by modulating the uptake of substrates and the activity of enzymes involved in aerobic glycolysis (Warburg effect), which enables them to adapt to the tumor microenvironment. However, increasing evidence suggests that mitochondrial metabolism, including the tricarboxylic acid (TCA) cycle, oxidative phosphorylation (OXPHOS), and glutaminolysis, is paradoxically activated in MYCN-amplified malignancies. Unlike non-amplified cells, MYCN-amplified cancer cells significantly promote OXPHOS-dependent ATP synthesis. Furthermore, tumor cells are differentially dependent on fatty acid β-oxidation (FAO) according to N-Myc status. Therefore, upregulation of FAO-associated enzymes is positively correlated with both N-Myc expression level and poor clinical outcome. This review explores therapeutic strategies targeting cancer stem-like cells for the treatment of tumors associated with MYCN amplification.